Specific detection of hypochlorite based on the size-selective effect of luminophore integrated MOF-801 synthesized by a one-pot strategy. Issue 8 (5th February 2019) - Ye, Yunxi; Zhao, Liwei; Hu, Shuanggang; Liang, Ajuan; Li, Yongsheng; Zhuang, Qixin; Tao, Guorong; Gu, Jinlou
Abstract : Intracellular hypochlorite could be rapidly and specifically detected with novel luminescent AF@MOF-801 nanoparticles based on a size-selective effect. Abstract : Hypochlorous acid (HClO), as one of the reactive oxygen species, plays a key role in a variety of physiological and pathological processes, while its accurate and specific in vitro monitoring remains a profound challenge. Herein, a novel luminescent metal–organic framework with high chemical stability has been designed for the specific detection of intracellular ClO − . The specificity was realized by the size-selective effect of MOF-801 with an ultra-small aperture, which can inhibit the entry of large-sized interferents into the cages of MOFs. A universal "ship in a bottle" approach has been proposed to construct this novel sensory platform, in which a large class of luminescent molecules containing carboxylic groups serve as modulators and combine with Zr6 clusters, eventually becoming the luminescent genes of these novel designed MOF-801. Luminescent molecules were readily locked in the framework since they were larger than the small pore entrance of MOF-801, skillfully solving the possible issue of dye leakage. By introducing active sites of 5-aminofluorescein (AF) into MOF-801 (AF@MOF-801) as an example, an excellent ClO − sensing probe was fabricated, which showed strong reliability and excellent sensing performance toward intracellular ClO − with an ultrahigh linear correlation of the Stern–Volmer equation, a rapid response time as short as 30 s and a limit of detection (LOD) as low as 0.05172 μM. Compared with the free AF molecular probe, the specificity of AF@MOF-801 NPs toward ClO − was scarcely affected by other possibly coexistent large-sized interferents in biosystems. The in vitro monitoring of ClO − was also tested with these newly developed AF@MOF-801 NPs, prefiguring their great promise as a robust imaging tool to disclose the complexities of ClO − homeostasis and its pathophysiological contributions.